Curdione and Schisandrin C Synergistically Reverse Hepatic Fibrosis via Modulating the TGF-β Pathway and Inhibiting Oxidative Stress - Dai, Wenzhang; Qin, Qin; Li, Zhiyong; Lin, Li; Li, Ruisheng; Fang, Zhie; Han, Yanzhong; Mu, Wenqing; Ren, Lutong; Liu, Tingting; Zhan, Xiaoyan; Xiao, Xiaohe; et al. (Frontiers in Cell and Developmental Biology, 2021)
Hepatic fibrosis is the final pathway of several chronic liver diseases, which is characterized by the accumulation of extracellular matrix due to chronic hepatocyte damage. Activation of hepatic stellate cells and oxidative stress (OS) play an important role in mediating liver damage and initiating hepatic fibrosis. Hence, hepatic fibrosis can be reversed by inhibiting multiple channels such as oxidative stress, liver cell damage, or activation of hepatic stellate cells. Liuwei Wuling Tablets (LWWL) is a traditional Chinese medicine formula with the effect of anti- hepatic fibrosis, but the composition and mechanism of reversing hepatic fibrosis are still unclear. Our study demonstrated that one of the main active components of the Chinese medicine Schisandra chinensis, Schisandrin C (Sin C), significantly inhibited oxidative stress and prevented hepatocyte injury. Meanwhile one of the main active components of the Chinese medicine Curdione inhibited hepatic stellate cell activation by targeting the TGF-β1/Smads signaling pathway. The further in vivo experiments showed that Sin C, Curdione and the combination of both have the effect of reversing liver fibrosis in mice, and the combined effect of inhibiting hepatic fibrosis is superior to treatment with Sin C or Curdione alone. Our study provides a potential candidate for multi-molecular or multi-pathway combination therapies for the treatment of hepatic fibrosis and demonstrates that combined pharmacotherapy holds great promise in the prevention and treatment of hepatic fibrosis.